Changing minds via collective action: Exposure to the 2017 Women's March predicts decrease in (some) men's gender system justification over time. (August 2018) - Saguy, Tamar; Szekeres, Hanna
Even though social change efforts are largely aimed at impacting upon public opinion, there is an overwhelming scarcity of research on the potential consequences of collective action. We aimed to fill this gap by capitalizing on the widespread 2017 Women's March that developed across the US and worldwide in response to Donald Trump's inauguration. We assessed changes in gender system justification of men and women over time—before and right after the Women's March ( N = 344). We further considered participants' level of gender identification and reported levels of exposure to the march as predictors of change. Results showed that gender system justification decreased over time, but only among low-identified men with relatively high exposure to the protests. For men highly identified with their gender, gender system justification actually increased with greater exposure to the protests. For women, we did not observe changes in gender system justification. Implications for collective action and for gender relations are discussed.